Forgotten in the diaspora: the Palestinian refugees in Egypt, 1948-2011 - Yassin, Lubna (AUC Knowledge Fountain, 2013)
The present thesis examines the question of how political tensions affect refugees’ rights through analyzing the course of Egyptian-Palestinian relations spanning the different Egyptian regimes. Political tensions here refer to instances when Palestinian factions either grew directly at odds with the Egyptian regime, or entangled within the web of regional struggle for power. This thesis examines how shifting political discourses and interests affected the civil rights of stateless refugees in a host country. The project addresses the securitization of the Palestinians with special emphasis on refugee status and regime stability. By researching official political narratives, this research interrogates the deployment of “national security” discourse and its impact on refugees’ basic civil rights, or denial thereof. This project explores if and how the Camp David Accords of 1978 and the Egyptian-Israeli Peace Treaty of 1979 changed the official Egyptian attitude towards the Palestinian refugees in Egypt. Other questions will include; how has Egypt’s status as a signatory to international and regional treaties related to the protection of the refugees affected the state’s policies regarding the Palestinian community? In this respect it is worth noting that Egypt ratified without reservations the Casablanca Accords of 1965 which stipulated that the Palestinian refugees in signatory Arab host countries should be treated as equals to nationals. The project will also address the role of the press in shaping public opinion and narratives on issues such as national security. The project will also explore the role of the press in pushing certain topics to the forefront while pulling others to the background. It will also address the question of how the Egyptian press constructs the image of the Palestinians with special emphasis on moments of political tensions between Egypt and the Palestinian factions (i.e. singing the Camp David Accords and the Peace Treaty, tensions rising between Egypt and Hamas across the Gaza Strip boarders). The research addresses the political shifts in Egypt for over six decades. It begins with an analysis of Nasser’s pan-Arabism. It then moves to Sadat’s nationalist oriented (Egypt First) discourse and his close ties with the West generally and the United States specifically. The thesis will then explore the Mubarak era, which is largely a continuation of Sadat’s legacy. This project contributes to the existing scholarship investigating protection gaps in refugees’ studies, since it examines how shifting political discourses or conflicting interests would affect enacting refugees’ civil rights in host countries. The research investigates the extent of the integration and implementation of the terms of regional and international treaties within the Egyptian domestic legal apparatus. It is worth mentioning that whenever Egypt signs a treaty whether regional or international it automatically becomes integrated into the Egyptian legal system the day following its publication in the official gazette. Thus, it is important to examine whether or not such treaties are effectively enacted and what are the obstacles hindering their implementation. In other words, the project examines the gap between refugees’ realities and theoretical protection mechanisms.